STIMULASI PEMBUNGAAN BUGENVIL (Bouganvillea spectabilis Willd) DENGAN RETARDAN DAN BERBAGAI KOMPOSISI MEDIA DALAM LINGKUNGAN JALAN YANG TERPOLUSI UDARA - Nizar Nasrullah; Yulia Mustika Wati; Devi Wahyuningtyas Utami (Jurnal Lanskap Indonesia, 2012)
Bougainvillea often found having no flower in polluted street area, and performs only leaves colors. This experiment aims to study flowering forcing on Bougainvillea using growth retardants and media modification inpolluted street area. The experiments were conducted in 2 series, first experiment was conducted in the vicinity of road shoulder of Jl. Yos Sudarso, Sunter North Jakarta to test the effects of 4 kind retar-dants (control, paclobutrazol 500 ppm, daminozide 6000 ppm, and chlormequate 6000 ppm), and 3 types media compositions of soils, dung and sand.Second experiment was conducted in the median of Jagorawi Toll Highway in Bara-nangsiang Bogor to test the effect of 4 concentrations of paclobutrazol (0, 250, 500, 700 ppm) and 3 types media compositions of soil, dung, sand or gravel on Bougainvil-lea flowering.The First experiment results showed that the end of experiments, treatment of paclo-butrazol 500 ppm performed the lowest of plant height in compared to the treatment of daminozide 6000 ppm and chlormequate 6000 ppm and control. The highest number of flower cluster and total number of flower were obtained in treatment of media of soils : dung : sand = 1 : 1 : 2 and in application of 500 ppm of paclobutrazol. Second experiments showed number of flower cluster, and total number of flower were found the highest value in the treatment of media ofsoil : dung : sand = 1 : 1 : 3, and among of paclobutrazol treatment the highest value were found in the treatment of 250 and 500 ppm, and the lowest value was found in the treatment of 700 ppm. Based on expe-riments results, its recommended to use media of soil : dung : sand = 1 : 1 : 3 or appli-cation of 250 ppm paclobutrazol to force flowering of Bougainvillea in polluted street area.